2013
DOI: 10.1093/schbul/sbt124
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Frontal Glutamate + Glutamine and N-Acetylaspartate Levels in Patients With Chronic Schizophrenia but not in Those at Clinical High Risk for Psychosis or With First-Episode Schizophrenia

Abstract: Changes in brain pathology as schizophrenia progresses have been repeatedly suggested by previous studies. Meta-analyses of previous proton magnetic resonance spectroscopy ((1)H MRS) studies at each clinical stage of schizophrenia indicate that the abnormalities of N-acetylaspartate (NAA) and glutamatergic metabolites change progressively. However, to our knowledge, no single study has addressed the possible differences in (1)H MRS abnormalities in subjects at 3 different stages of disease, including those at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
76
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 82 publications
2
76
1
Order By: Relevance
“…Purdon et al (2008) finding the absence of differences in Glu metabolites levels between HR and HC in the same brain region, as was for Yoo et al (2009). Concordantly, analyzing the medial-PFC in HR subjects, EP and schizophrenia patients, Natsubori et al (2014) revealed significant decrease in Glu metabolites only in the schizophrenia group.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Purdon et al (2008) finding the absence of differences in Glu metabolites levels between HR and HC in the same brain region, as was for Yoo et al (2009). Concordantly, analyzing the medial-PFC in HR subjects, EP and schizophrenia patients, Natsubori et al (2014) revealed significant decrease in Glu metabolites only in the schizophrenia group.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, recent studies have shown decreased Glu levels in schizophrenia patients when compared to healthy individuals, particularly in medial frontal region (Marsman et al 2013). Moreover, chronicity in schizophrenia was found to be related to decreased prefrontal Glu (Natsubori et al 2014), Glx (Glu + Gln) and NAA levels (Liemburg et al 2016); with evidence for a time-depending role for Glu (Merritt et al 2016), whereas findings in early psychosis (EP) are still controversial (for a review see Treen et al 2016). While the studies presented above provide evidence that THC leads to glutamatergic dysfunction, they do not unequivocally identify the specific brain circuits or regions involved.…”
Section: Introductionmentioning
confidence: 88%
“…[26][27][28][29][30] However, the quality of the spectral fits is not always clear in these reports (except for [27][28][29] ) and the samples were small (9 to 30 for the schizophrenia groups 6 ). More recent studies reported increases, [31][32][33][34][35] reductions 25,[36][37][38] and no differences 39 in Glx or glutamate. Two 33,34 of the 5 recent studies documenting elevations involved more ventral regions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent in vivo 1 H magnetic resonance spectroscopy ( 1 H-MRS) data support altered glutamate and glutamine levels in the brains of schizophrenia patients (De la Fuente-Sandoval et al, 2011;Marsman et al, 2013;Natsubori et al, 2013). Furthermore, both acute and repeated exposure to NMDA receptor antagonists can induce schizophrenia-like symptoms in humans (Cosgrove and Newell, 1991;Krystal et al, 1994) and acute treatment with the NMDA receptor antagonist ketamine exacerbates the symptoms of schizophrenia patients (Lahti et al, 2001;Malhotra et al, 1997).…”
Section: Introductionmentioning
confidence: 99%